Religion-Market Theory: A Qualitative Theory Testing - Nouha Khelfa (Indonesian Journal of Religion and Society, 2023)
Despite industrialization and modernization, religion still has a significant impact on society and politics. Many theories compete to answer questions about religion, yet this paper argues that religion-market theory has superiority in explaining the failure of secularization to diminish religion even in the most developed nations such as the United States, while it succeeded in others. Relying on Mill’s method of difference, this study qualitatively compares the two cases of the United States and the United Kingdom, relying on the history of religion and the economic structures of religious institutions. This study proves that Americans are far more religious than the British because since the foundation of the republic, the U.S. has not adopted any state religion while the UK has Christianity as the religion of the state since the English Reformation. Hence, religion-market theory that links between state’s regulations of religion and religiosity proves its superiority again.